2018
DOI: 10.1364/oe.26.006817
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency sub-watt in-band-pumped single-frequency DBR Tm3+-doped germanate fiber laser at 1950 nm

Abstract: Based on a 1.8-cm-long heavily Tm-doped germanate fiber and being in-band-pumped by a 1610 nm single-mode laser, a high-efficiency and high-power single-frequency distribute Bragg reflector (DBR) fiber laser emitting at 1950 nm is demonstrated. The DBR fiber laser has a maximum output power of ~617 mW and a slope efficiency for the absorbed pump power reaches to more than 42.2%. A stable single-longitudinal-mode laser output with a signal-to-noise ratio of greater than 63 dB is realized. The measured relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The maximum output power of 617 mW was achieved with a slope efficiency of 42.2%. The output signal-to-noise ratio was up to 63 dB and the 3-dB linewidth was 12.55 kHz [20]. Ring cavity has also been developed for high-power single-frequency fiber laser demonstration.…”
Section: High-power Single-frequency Fiber Oscillatorsmentioning
confidence: 99%
“…The maximum output power of 617 mW was achieved with a slope efficiency of 42.2%. The output signal-to-noise ratio was up to 63 dB and the 3-dB linewidth was 12.55 kHz [20]. Ring cavity has also been developed for high-power single-frequency fiber laser demonstration.…”
Section: High-power Single-frequency Fiber Oscillatorsmentioning
confidence: 99%
“…After decades of research, SFFLs have found a variety of uses in optical sensing, optical measurement, and coherent optical communication. [1][2][3][4][5] The most commonly used configurations for SFFLs include the construction of distributed feedback (DFB) fiber lasers, [6][7][8] distributed Bragg reflector (DBR) fiber lasers, [9][10][11][12][13][14] and ring-cavity fiber lasers with ultranarrow-bandwidth filters. [15][16][17] However, the DBR and DFB fiber lasers cannot efficiently absorb the pump power and also need accurate and costly fiber Bragg gratings (FBGs), whilst the ring-cavity fiber lasers have a complex and unstable structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, based on heavily rare earth‐doped, multicomponent oxide glass fibers, single‐frequency output power of short‐cavity fiber lasers has reached the level of hundreds of milliwatts with wavelengths in the 1, 1.5, and 2 μm regime. [ 12–14 ] However, issues such as spatial hole burning and gain saturation still limit the power scaling of these short‐cavity lasers. Polynkin et al reported a single‐frequency, short‐cavity oscillator at 1.5 μm using a twisted‐mode cavity to eliminate spatial hole burning and achieved an output power of 1.9 W. [ 15 ] Following this work, the same group used a 3.8 cm‐long photonic crystal, phosphate glass fiber with a highly erbium‐doped large‐area core to avoid gain saturation.…”
Section: Introductionmentioning
confidence: 99%